Understanding the Diversity of User Requirements for Interactive Online Health Services - Banna, Sumayya (2016)
The purpose of the study presented in this paper is to develop our understanding of the diversity of user requirements for interactive online health services in order to inform improvements to their design leading to better health outcomes. Data collected in Australia was analysed following the established but unfamiliar regime of Q methodology that enables the subjectivities of a diverse set of respondents to be studied systematically. This analysis produced three significant groupings of respondents referred to as: 'service-oriented users', 'collaborative interactive users' and 'health information seekers'. Among these groups we identify and discuss a range of elements indicative of the variety of users' experiences and subjective views on the content, design, functionality and usability of systems for the development of effective interactive online health service provision.